SWOT Analysis And Analytical Hierarchy Process (AHP) To Determine A Sustainable Development Strategy In Indonesia's National Defense Industry - Ali Mashudi; Moeljadi Moeljadi; Herman S.; Alfi Haris Wanto (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Improving national defense can be done by strengthening the national defense industry. A strong defense industry will produce modern and sophisticated military equipment according to user needs. The large number of military equipment imported from abroad requires efforts to increase the domestic defense industry to meet the needs of military equipment to increase defense capabilities. The purpose of this study is to analyze strategies and programs for the development of the defense industry and to analyze several factors that play a role in the development of the national defense industry. The collection technique in this research is through Focus Group Discussion, the results of which are input for SWOT and AHP analysis. The results of the SWOT analysis show that the defense industry has a strong category of competitiveness, and has a high opportunity to be developed because it has its own market. The three main factors for the sustainability of the defense industry are: the capability of the defense industry, the quality of its human resources, and the accuracy of delivery.